Owen Jones, Gottfried Semper and the anthropological origins of ornamental art - Braga, Ariane Varela (2020)
Following the first London Universal Exhibition in 1851, architects Owen Jones and Gottfried Semper appealed to primitive cultures to affirm the anthropological nature of ornamental art.